TOLERAR/TOLERANCIA: TRANSFORMATIONS OF THE FUNDAMENTAL MEANINGS IN THE SPANISH POST-CHRISTIAN SOCIETY - G. . Gorenko (Ибероамериканские тетради)
The article presents lexicographical analysis of words “tolerar” and “tolerancia” in Spanish, which allows us to follow paths of transformation of their fundamental meanings. Considered semantic changes are a reflection of deep processes that occur in the Spanish post-Christian society.